(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
Palm olein is widely used for domestic and commercial frying but its usage beyond recommended cycle might lead to spoilage. Therefore, this study focuses on the comprehensive analysis of chemical and physical properties of recycled palm olein. It was prepared by frying potato strips up to 5 cycles with potato (g)-to-oil (ml) ratio of 3/20 prior to physico-chemical analysis. The temperature profile of RBD palm olein throughout frying also been investigated. It was done by taking the palm olein temperature during the frying of potato strips within 15 minutes for each cycle. There were physico-chemical analyses included colour measurement, viscosity, iodine value, peroxide value, moisture content, contact angle and density. However, according to the present result, peroxide value and contact angle was quite unsuitable or weak for the oil spoilage analysis for the first 5 cycles. Whereas moisture content, colour measurement, density, viscosity and iodine value were insignificant (p>0.05) for all cycles. Thus, those results could not be considered as definite indicators for spoilage assessment. This might be due to the starch composition within the potato strips that shows no changes despite 5 frying cycles. For that reason, further analysis (greater than 5 cycles) is needed to confirm at which oil cycle of that oil should become spoiled.